Evaluating the Relationship between HSE Management and Job Satisfaction and Performance Quality among the Production Center (Employees of Hacoupian Clothing Industrial ‎Company: A Case Study) - Hamid AKBARI; Fahimeh SARBANDI (Shahid Sadoughi University of Medical Sciences, 2022)
Introduction: The productivity of an organization is closely related to the improvement of the safety and health of employees and the development of knowledge and skills of human resources in advancing the organization goals. Based on a combination of questionnaire and survey, this study examines the impact of implementing safety management practices on the performance and job satisfaction of employees in Iran's production units. Research Method: This descriptive-cross-sectional study was conducted in 1400 on 200 employees and managers of the Hacoupian clothing industrial company located in Tehran province. 130 of them were selected based on random sampling using the Morgan table. Data collection tools included a researcher-made questionnaire, which was further confirmed by experts by applying their opinions regarding its validity and reliability. It was approved by experts. The analysis method in this study is mainly descriptive and the type of research is relational. Data and research hypotheses were respectively tested using Structural equation modeling (SEM) and Partial least squares (PLS) approach through SPSS26 software. Results: Findings showed the appropriate fit of measurement and structural models. In addition, results demonstrated the positive effect of improving safety on the job satisfaction of employees in production units, as well as the negative effects of not paying attention to the health of the working environment on the quality of employees' performance. Conclusion: The more companies and governments pay attention to the issue of operational health and safety, the organizational and environmental situation will be formed in such a way that it will optimally motivate employees and increase the quality of production and operations in the organization.